PENGARUH PEMAHAMAN AKUNTANSI, PENERAPAN STANDAR AKUNTANSI KEUANGAN DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PADA PT. INDOMARCO ADI PRIMA BENGKULU - Jati, Rio Linggar; Helmi, Helmi Herawati; Iwin, Iwin Arnova (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
The purpose of this research is to enhance public knowledge about accounting, financial accounting regulations, and how Codexda quality of financial reports is influenced by the internal control system. PT Indomarco Adi Prima in Bengkulu is the object of the research. This study uses a quantitative approach. 51 employees of PT Indomarco Adi Prima located in Bengkulu were asked to fill out a survey. Then, the collected data were analyzed using multiple linear regression. This was done using version 26 of the SPSS program. The results of this study indicate that three factors (X1) affect the quality of financial statements: accounting knowledge (X1), application of accounting principles (X2), and internal control systems (X3). These three components are interrelated, and the adjusted R2 value of 0.247 indicates that they contribute 24.7% to the change in the quality of financial statements. Therefore, researchers are advised to consider other factors that may influence the quality of PT Indomarco Adi Prima Bengkulu's financial statements, such as employee performance and information technology.